2021
DOI: 10.1177/11206721211053167
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes and keratoconus—a systematic review and meta-analysis

Abstract: Purpose To assess the association between diabetes mellitus and keratoconus. Methods PubMed, Google Scholar, Web of Science, and Scopus databases were searched for literature on the association between diabetes and keratoconus. The last literature search was conducted on April 4, 2021. A secondary form of the literature search was conducted by manually scanning the reference list of retrieved eligible articles. Included studies were cohort, case-control, or cross-sectional study design that used odds ratio or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, a potential correlation between diabetes mellitus as systemic comorbidity and KCN is a much debated topic in the current literature. 30–32 Although type 2 diabetes mellitus has been found to be potentially correlated with KCN, 32 only a small percentage of patients in our cohort had DM. This would be consistent, however, with a recent systematic review and meta-analysis that found no correlation between diabetes and KCN.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Furthermore, a potential correlation between diabetes mellitus as systemic comorbidity and KCN is a much debated topic in the current literature. 30–32 Although type 2 diabetes mellitus has been found to be potentially correlated with KCN, 32 only a small percentage of patients in our cohort had DM. This would be consistent, however, with a recent systematic review and meta-analysis that found no correlation between diabetes and KCN.…”
Section: Discussionmentioning
confidence: 76%
“…This would be consistent, however, with a recent systematic review and meta-analysis that found no correlation between diabetes and KCN. 30 Our study is not without limitations. Although the first documented visit in the EHR was designated as a patient's baseline presentation, many of these patients may have had a history of KCN before the initial presentation to our institution, which has multiple sites including the community and tertiary care hospital-based referral centers.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, several meta-analyses have examined the association between keratoconus and diabetes. One such analysis examined 6 case–control studies and 3 cohort studies and found no significant association between keratoconus and DM, with an odds ratio of 0.87 and a 95% confidence interval of 0.66–1.14 [ 125 ]. Another meta-analysis examining 2 additional case–control studies for a total of 8 case–control and 3 cohort studies also determined no significant association between keratoconus and DM, with an odds ratio of 0.83 and 95% confidence interval of 0.66–1.10 [ 126 ].…”
Section: Resultsmentioning
confidence: 99%